Etiology and maternofetal issue of acute pulmonary edema in prepartum at the Befelatanana university hospital of gynecology and obstetrics - Romuald, Randriamahavonjy; Tanjona, Ratsiatosika A.; Fleurian, Sidy; Housni Ibrahim, Housni Ibrahim (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pulmonary edema is defined as the as the ultrafiltration of plasma through the capillary wall to the interstitium and pulmonary alveoli. It is a rare pathology and difficult diagnosis. Through this study, we wanted to know the etiologies and maternofetal issue of acute pulmonary edema manifesting in prepartum. It is a rare pathology and difficult diagnosis. Through this study, we wanted to know the causes and maternofetal issue of acute pulmonary edema manifested in prepartum. Methods: It is about a descriptive retrospective study from January 1st, 2014 to April 30th, 2018 at the Befelatanana University Hospital of Obstetrics and Gynecology. We included all pregnant patients of 20 weeks and above with acute antepartum pulmonary edema. We excluded postpartum APE. Data collection and analysis was performed on the Excel Stat 2007 Software. Results: We had 36 cases of acute pulmonary edema during this period with an incidence of 0.001%. The average age was 28.75±8.72 years. Mean gestational age was 32 ± 7.82SA. Pregnancy was poorly followed in more than half of the cases. 15% did not perform prenatal follow-up. Caesarean section was the chosen delivery route in 82% of cases. Among the childbirth, 73% were premature, 63% asphyxiated and 56% hypotrophic. We had 52% of maternal death and 44, 44% of fetal loss. The main etiology was dominated by preeclampsia and its complications (63.88%) followed by cardiopathy (25%). A case of malaria during pregnancy was identified as the cause of APE. Conclusions: Acute pulmonary edema during pregnancy is a serious pathology because the maternal prognosis is catastrophic with 50% maternal and foetal mortality in our context. The identification of patients at risk, the monitoring of pregnancy, the effective management of the pathology involved are necessary to reduce the incidence and maternal mortality secondary to pulmonary edema.